Falling in - Dowell, Frances O'Roark (Atheneum Books for Young Readers, 2010)
Middle-schooler Isabelle Bean follows a mouse's squeak into a closet and falls into a parallel universe where the children believe she is the witch they have feared for years, finally come to devour them.